2002
DOI: 10.1037/0022-006x.70.4.1040
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of body image dissatisfaction among overweight women seeking weight loss.

Abstract: Predictors of body image dissatisfaction (BID) among obese people are poorly understood. In 79 obese women seeking weight reduction, associations with BID of self-esteem, youth teasing, adult teasing, and internalization of sociocultural appearance standards (ISAS) were studied. Analyses revealed that only self-esteem, adult teasing, and ISAS predicted BID. Results highlight the importance of adulthood self-esteem and interpersonal-cultural context--rather than childhood experiences--in predicting adulthood BI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
58
1
8

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(78 citation statements)
references
References 26 publications
(39 reference statements)
10
58
1
8
Order By: Relevance
“…2,3,5,16,18,19,26,27 The results of this study confirm the strong association between BE and women who present BMI higher than 25 kg/m² among university students.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…2,3,5,16,18,19,26,27 The results of this study confirm the strong association between BE and women who present BMI higher than 25 kg/m² among university students.…”
Section: Discussionsupporting
confidence: 78%
“…15 Several studies have found an association between overweight or obesity and the presence of BE, showing values ranging from 15 to 63% in obese women who seek weight reduction programs. 2,3,5,[16][17][18][19] The present study aimed to investigate the prevalence of BE among female university students in different fields of study (exact sciences, health and humanities) and its association with body mass index (BMI) and age.…”
mentioning
confidence: 99%
“…This scale has received considerable support in its validity and reliability, including adequate internal consistency and test-retest reliability (36,37). The BSQ, BDI, and RSES are widely used measures of body image dissatisfaction and general psychosocial functioning in diverse clinical samples of obese patients (38)(39)(40)(41)(42), including bariatric surgery patients (43)(44)(45)(46)(47), and have been found to be associated with eating-related pathology within this latter group (25,26,48,49). The EOQ was included as an additional exploratory measure since eating (or overeating) in response to emotions is not uncommon for individuals who struggle with their eating behavior.…”
Section: Procedures and Assessment Measuresmentioning
confidence: 99%
“…Much of the literature on weight-based teasing has shown untoward effects on body dissatisfaction, selfesteem and disordered eating, including bulimic eating behaviour (6,10,11). However, many studies relied on clinical samples in adults (12)(13)(14) and virtually all were conducted in the United States; thus, the results may not be generalizable to adolescents in the Ottawa (Ontario) area. In a large study (15) of Canadian children, a strong association was found between aggression (in the form of bullying) and overweight and obese school children.…”
mentioning
confidence: 99%